Effect of non-surgical periodontal treatmenton salivary IL-13 levels in periodontitis with andwithout type 2 diabetes - YILDIRIM, HATİCE SELİN; İYİGÜN, SEZGİ; DOĞAN, BAŞAK (My University, 2022)
Background & Aim: Interleukin (IL)-13 is an anti-inflammatory and fibrogenic cytokine activated by T helper 2 cells. It has been shown that IL-13 inhibits pro-inflammatory cytokine synthesis and osteoclastogenesis. The aim of the study was to determine the effect of non-surgical periodontal treatment (NSPT) on salivary IL-13 levels in periodontitis patients with and without type 2 diabetes mellitus (T2DM). Methods: A total of 48 subjects, 12 systemically and periodontally healthy (H), 12 periodontitis with well controlled T2DM, 12 periodontitis with poorly controlled T2DM and 12 systemically healthy periodontitis, were recruited for the study. All periodontitis patients belonged to either Stage III or IV periodontitis. At baseline, all clinical parameters including plaque index, gingival index, bleeding on probing, probing depth and clinical attachment loss were recorded, and the saliva samples were collected from all subjects, at 3 months following the NSPT only from periodontitis groups. Salivary IL-13 levels were analysed by enzyme-linked immunosorbent assay. This study was supported by the grant from Marmara University Scientific Research Projects Coordination Unit #SAG-A-080519-0172. Results: All clinical parameters were higher in all periodontitis groups than the healthy subjects at baseline (p < 0.05) and improved 3 months after NSPT in all periodontitis groups (p < 0.05). At baseline, salivary IL-13 levels were lower in all periodontitis groups compared to H group (p < 0.05) but were similar among 3 periodontitis groups (p > 0.05). At 3 months following NSPT IL-13 levels were increased in all 3 periodontitis groups compared to baseline (p < 0.05). Conclusions: This study has revealed that low levels of salivary IL-13 are associated with periodontitis not T2DM. IL-13 may be used as a biomarker for both the diagnosis and treatment of periodontitis.